2019
DOI: 10.1186/s12862-018-1333-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sky islands generate highly divergent lineages of a narrowly distributed stream salamander (Pachyhynobius shangchengensis) in mid-latitude mountains of East Asia

Abstract: BackgroundClimate oscillation may have a profound effect on species distributions, gene flow patterns and population demography. In response to environmental change, those species restricted to montane habitats experienced expansions and contractions along elevation gradients, which can drive differentiation among sky islands.ResultsThe Shangcheng stout salamander (Pachyhynobius shangchengensis) is a cool stream amphibian restricted to high-elevation areas in the Dabie Mountains, East China. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 82 publications
7
88
0
Order By: Relevance
“…In this study, although O. tormota is a narrowly distributed species, each population still harbored relatively high levels of genetic diversity compared with other narrowly distributed amphibia (Table ), such as the Majorcan midwife toad ( Alytes muletensis ) in the mountainous regions of Majorca, red‐bellied newt ( Taricha rivularis ) in northern California in the United States, Sonoran tiger salamander ( Ambystoma mavortium stebbinsi ) in the San Pedro River of Arizona in the United States, Leora's stream salamander ( A. leorae ) in Iztaccihuatl‐Popocatepetl National Park of Mexico, Fourche Mountain salamander ( Plethodon fourchensis ) in the Ouachita Mountains of the central United States, and dwarf black‐bellied salamander ( Desmognathus folkertsi ) in the United States (Kraaijeveld‐Smit et al ., ; Shepard & Burbrink, ; Wooten, Camp & Rissler, ; Reilly et al ., ; Storfer et al ., ; Sunny et al ., ). In addition, the O. tormota genetic diversity was slightly lower than that of the Shangcheng stout salamander ( Pachyhynobius shangchengensis ) in the Dabie Mountains of eastern China and the Leishan spiny toad ( Leptobrachium leishanense ) in south‐western China, which were described having high genetic diversity (Zhang et al ., ; Pan et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In this study, although O. tormota is a narrowly distributed species, each population still harbored relatively high levels of genetic diversity compared with other narrowly distributed amphibia (Table ), such as the Majorcan midwife toad ( Alytes muletensis ) in the mountainous regions of Majorca, red‐bellied newt ( Taricha rivularis ) in northern California in the United States, Sonoran tiger salamander ( Ambystoma mavortium stebbinsi ) in the San Pedro River of Arizona in the United States, Leora's stream salamander ( A. leorae ) in Iztaccihuatl‐Popocatepetl National Park of Mexico, Fourche Mountain salamander ( Plethodon fourchensis ) in the Ouachita Mountains of the central United States, and dwarf black‐bellied salamander ( Desmognathus folkertsi ) in the United States (Kraaijeveld‐Smit et al ., ; Shepard & Burbrink, ; Wooten, Camp & Rissler, ; Reilly et al ., ; Storfer et al ., ; Sunny et al ., ). In addition, the O. tormota genetic diversity was slightly lower than that of the Shangcheng stout salamander ( Pachyhynobius shangchengensis ) in the Dabie Mountains of eastern China and the Leishan spiny toad ( Leptobrachium leishanense ) in south‐western China, which were described having high genetic diversity (Zhang et al ., ; Pan et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This phenomenon has also been observed in species from mid‐latitude Europe, such as the Maltese wall lizard ( Podarcis filfolensis ; Salvi et al ., ) and Italian wall lizard ( P. siculus ; Senczuk et al ., ). Our study further showed that some temperate species in mid‐latitude regions that are insensitive to environmental changes may have undergone attenuated glacial population contractions, or even experienced population expansion (Salvi et al ., ; Senczuk et al ., ; Pan et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations